Brazil as an economic superpower? : understanding Brazil's changing role in the global economy - Brainard, Lael; Martinez-Diaz, Leonardo, 1976- (Washington, D.C. : Brookings Institution Press, 2009)
"Brazil is once again getting attention in the northern hemisphere--attention long overdue, given its huge and diverse population, its physical size and diversity, and its geopolitical and economic importance as the largest country in Latin America. Long seen as an economic backwater, Brazil now occupies key niches in energy, agriculture, service industries, even high technology markets. Yet the nation still struggles with endemic problems of inequality and with a traditional ambivalence toward deep integration with the world economy. Brookings gathered scholars and policymakers from Brazil, Europe, and the United States to examine the present state and likely future of Brazil's economy. Their findings can be found in Brazil as an Economic Superpower? The authors' analysis focuses particularly on five key topics: agribusiness, energy, trade, social investment, and multinational corporations. The net result is an invaluable analytical contribution and a provocative look into the future of our global economy and into the workings of one particularly important component of that system"--Provided by publisher
Brazil : the "B" belongs in the BRICS / Lael Brainard and Leonardo Martinez-Diaz -- Brazil as an agricultural and energy superpower. Brazil as an international energy player / Ricardo Ubiraci Sennes and Thais Narciso -- Brazil as an agricultural and agroenergy superpower / André Meloni Nassar -- Brazil : the challenges in becoming an agricultural superpower / Geraldo Barros -- Opening markets : Brazil's trade policy. Brazil's trade policy : moving away from old paradigms? / Pedro da Motta Veiga -- Brazil's trade policy : old and new issues / Mauricio Mesquita Moreira -- Extending Brazilian multinationals' global reach. Big business in Brazil : leveraging natural endowments and state support for international expansion / Ben Ross Schneider -- Technology, public policy, and the emergence of Brazilian multinationals / Edmund Amann -- Brazil as an equitable opportunity society. Income policies, income distribution, and the distribution of opportunities in Brazil / Marcelo Neri.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Brazil -- Economic policy -- 2003-; Brazil -- Commercial policy; International business enterprises -- Brazil; Brésil -- Politique économique -- 2003-; Entreprises multinationales -- Brésil.; BUSINESS & ECONOMICS -- International -- General; BUSINESS & ECONOMICS -- International -- Economics; Commercial policy; Economic policy; International business enterprises; Brazil; Wirtschaftsentwicklung; Brasilien; Wirtschaftsentwicklung; Multinationales Unternehmen; Wirtschaftspolitik; Handelspolitik; Brasilien; International business enterprises -- Brazil; Brazil -- Economic policy -- 2003-; Brazil -- Commercial policy; Since 2003; Aufsatzsammlung